PENGARUH KECERDASAN EMOSIONAL, SELF EFFICACY DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMA NEGERI 13 TANGERANG - Oneng Dyah Rumantyeng; Tjiptogoro Dinarjo Soehari (Akademika : Jurnal Teknologi Pendidikan, 2016)
This thesis aims at up aware of the influence of emotional intelligence (emotional intelligence), teacherefficacy (self efficacy), and job satisfaction (job satisfaction) against the performance of the teacher in SMA Negeri13 Tangerang. The population in this study there were 50 teachers in place of research, and the research sample is44 people, the determination of the amount of this in accordance with the provisions of sampal of theory research.Adeyano research findings, et.al, (2013), which proved influential teacher efficacy are positively andsignificantly to the performance of teachers, likewise also with research results from the Shah, et.al, (2012), foundthat job satisfaction is positive and significant effect on performance of teachers. The methods used in this researchis a survey method, where researchers want to find out the influence of one variable with another variable, eitherpartially or simultaneously by analyzing data correlation and Linear Regression Analysis, use the StatisticalProduct and Service Solution or SPSS version 22.0.The Results of research obtained variabel teacher efficacy, job satisfaction is proven to provide a positiveand significant influence on performance of teachers, while for positive emotional intelligence influential variablessimultaneously against the performance of teachers in high school Negeti 13 Tangerang. Thus these three variablesare: emotional intelligence, efficacy and teacher job satisfaction simultaneously (with – the same) also proved to bea significant and positive effect on performance teacher at SMA Negeri 13 Tangerang